Polypropylene membranes with surface modification for separation of n-hexane/oil - Harshita Dihora; Pranay Kumar; Vishal Gohil; Nayan Nandha; Mrinmoy Mondal; Puyam S. Singh (Chemical Engineering Journal, 2026)

Multi-criteria geospatial assessment of urban land suitability for resilient development in Nagpur, India - Shailendra Yadav; Anirban Mandal; Pranay Taywade (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Evolution of intelligent nitrogen management systems: a two-decade global research analysis - Manojit Chowdhury; Suman Dutta; Karishma Kumari; Ayushi Jha; Krishna Mondal; Dhananjay Paswan Das; Pranay Sarkar; Ajay N. Satpute; Subrata Gorain; Vishal Gupta (Computers and Electronics in Agriculture, 2026)

Nanofiltration hollow fiber membranes: Fabrication strategies and applications in water treatment – A review - Pranay Kumar; Nayan Nandha; Mrinmoy Mondal; Puyam S. Singh (Journal of Water Process Engineering, 2026)

Spatio-temporal assessment of ecological restoration in the Jharia Coalfield using multi-temporal Landsat data and spectral indices - Pranay Ramesh Moon; Manas Das; Debasish Sing; Soumyadip Biswas; Amit Kumar Mankar; Radhakanta Koner (Journal for Nature Conservation, 2026)

An atlas of geological carbon sequestration potential in CBM-rich coalfields of India - Vikram Vishal; Debanjan Chandra; Bankim Mahanta; Pranay; George Koperna; Shaswattam; Vani G．D．; Bodhisatwa Hazra; Suprotim Ganguly; Anwesa Das; Mayank Ahuja; Sayan Ghosh; et al. (International Journal of Greenhouse Gas Control, 2026)

Green-engineered Ag-Ni-Co trimetallic nanocomposite: a unified platform for visible-light photocatalysis and bioactivity - Pavan Sai Nagilla; Sai Prudhvi Karanam; Nithin Krishna Nagella; Yasaswi Khaderbad; Naveen Kumar Dabbeta; Pranay Bhasker Kalakonda; Balaji Pandya; Vijay Morampudi; Krishnakumar Balu; Parvathalu Kalakonda (Nanotechnology for Environmental Engineering, 2026)

Gas chromatography–mass spectrometry analysis of the secondary metabolites produced by Bacillus paramycoides BOK01 and Microbacterium barkeri BPATH02 and investigation of their antifungal activity against tea pathogens - Pranay Raj; Harshit Kumar Sharma; Venkatesan Selvaraj; Abhay Kumar Pandey (Antonie van Leeuwenhoek, 2026)

Leopard sterilisation in India: The ecological and ethical costs of anthropocentric wildlife management - Pranay Arora (Ambio, 2026)
India’s rising human–leopard conflict has prompted the government to adopt immune contraceptives to manage leopard populations. The decision has sparked debate among wildlife experts and conservation organisations, government officials, and local communities. Here, I discuss the ecological and ethical implications of this intervention and highlight alternative, coexistence-based approaches that recognise both humans and wildlife as stakeholders within shared socio-ecological systems.

Comprehensive field-based hazard assessment and mitigation strategies of glacial lakes in the Eastern Himalaya - R. K. Sharma; Rajeev Rajak; Sandeep Tambe; Pranay Pradhan; Narpati Sharma; Baichung Lepcha; Priya Pradhan; Rajesh Kumar; Dhiren G. Shrestha; Dharmendra Lamsal; Sajan Poudyal; Tenzing D. Bhutia; et al. (Natural Hazards, 2026)

Pathological and molecular characterization identified Muyocopron laterale as a new pathogen causing brown leaf spot disease of tea in India - Harshit Kumar Sharma; Pranay Raj; Sajeewa S. N. Maharachchikumbura; Abhay Kumar Pandey (Journal of Plant Diseases and Protection, 2026)

Unraveling salinity, heat and their interactive effect on three contrasting rice genotypes at their seedling stages: Insights from growth, physiology and redox homeostasis - Kongkong Mondal; Pritamjit Konar; Dip Pal; Sandip Pal; Pranay Senapati; Arijit Ghosh; Suvranil Dutta; Nilabhra Ghosh; Sanjeevan Paul; Bijan Adhikari; Narottam Dey (Biocatalysis and Agricultural Biotechnology, 2026)

Spatialization of Aquacrop Model Using Remote Sensing for Soyabean Yield Estimation for Nanded District of Maharashtra - A. Rajani; H. R. Shwetha; Murali Krishna Gumma; Pranay Panjala; Roja Mandapati (Journal of the Indian Society of Remote Sensing, 2026)

Soil microorganisms in the age of plastic pollution: effects of micro- and nano-plastics on soil health - Devendra Kumar; Archana T. S.; Richard Singh Hijam; Pranay; Vipul Kumar (Environmental Science and Pollution Research, 2026)

Integrating DEM and flow stress factors to identify sedimentation-transportation zone in the eastern Himalayan foothill region - Rakesh Das; Pranay Paul; Moumita Saha; Rumki Sarkar (Science of The Total Environment, 2026)

Exploring the Global Trend of the Sustainable Bioeconomy: An Analysis of Scientific Literature - Reena Kumari; Pranay Parashar (Circular Economy and Sustainability, 2026)

Synaptic aging and neurodegeneration: the role of synaptic vesicle dynamics and neurotransmitter imbalance - Pranay Wal; Abhijit Dutta; Talha Jawaid; Mujeeb Ur Rahman; Gowri Krishnaperumal; S. Renuka Jyothi; Irwanjot Kaur; Shaker Al-Hasnaawei; Aashna Sinha; Laxmidhar Maharana; Sourav Debnath; Pratap Kumar Patra; et al. (Biogerontology, 2026)

Solvent-resistant modified polypropylene membranes for edible oil degumming - Harshita Dihora; Pranay Kumar; Vishal Gohil; Nayan Nandha; Mrinmoy Mondal; Puyam S. Singh (Journal of Environmental Chemical Engineering, 2026)

Biogenic Synthesis and Optimization of Lantana Montevidensis-Mediated Silver Nanoparticles as a Multifunctional Therapeutic: Anti-Inflammatory and Cytotoxicity Evaluation - Sourabh Malabade; Preeti Salve; Pranay Shirke; N. A Khatib (Journal of Pharmaceutical Innovation, 2026)

Global plastic treaty collapses due to industry pressure: What can we learn from the tobacco control treaty - Pranay Lal; Amit Yadav; Yogesh Pratap Singh (Ambio, 2026)

Biocompatible Ocular Films: A Novel Approach to Prolonged Aceclofenac Release and Mucoadhesion - Jyotsana Dwivedi; Namra Aziz; Pranay Wal; Abhishek Bhattacharjee; Mohd Imran; Pankaj Nainwal (Journal of Pharmaceutical Innovation, 2025)

Retraction Note: Nanosilver-functionalized polysaccharides as a platform for wound dressing - Syam Mohan; Pranay Wal; Kamla Pathak; Madhusmruti Khandai; Tapan Behl; Hassan A. Alhazmi; Gulrana Khuwaja; Asaad Khalid (Environmental Science and Pollution Research, 2025)

Genome mining of carbohydrate-active enzymes (CAZyme) and poly-γ-glutamic acid (γ-PGA) synthesis by Bacillus velezensis (WA11) directly from lignocellulosic biomass-based substrate - Rakeshkumar Yadav; Pranay Awathare; Pushkar Shitut; Vaishnavi Mahajan; Pranav Nair; Mahesh Dharne (Biocatalysis and Agricultural Biotechnology, 2025)

Assessing public health risks from crop residue burning: a spatiotemporal case study in Telangana, India - Pranay Panjala; Murali Krishna Gumma; Shashi Mesapam (Air Quality, Atmosphere & Health, 2025)

SDGs beyond 2030: shaping the future with lessons from the past - Pranay Arora; Tahmish Fatima; Naveen Kumar Arora (Environmental Sustainability, 2025)

One-step design, characterization, and performance evaluation of g-CN-polysulfone mixed-matrix hollow fiber membranes for efficient wastewater dye removal - Pranay Kumar; Nayan Nandha; Mrinmoy Mondal; Puyam S. Singh (Journal of Water Process Engineering, 2025)

Computational studies of natural product compound (CP-225917) for lead identification - N. S. Hari; NS Hari Narayana Moorthy; Akhilesh Tiwari; Pranay Soni; E. Manivannan; C. Karthikeyan (In Silico Pharmacology, 2025)

First report on analysis of chemical space, scaffold diversity, critical structural features of HDAC11 inhibitors - Rinki Prasad Bhagat; Jyotisha; Indrasis Dasgupta; Sk. Abdul Amin; Pranay Jakkula; Arijit Bhattacharya; Insaf Ahmed Qureshi; Shovanlal Gayen (Molecular Diversity, 2025)

Effects of CO2 and H2O saturation on physico-mechanical attributes of bituminous coal - Pranay Vilas Bhapkar; Sarada Prasad Pradhan; Mohd Sharique Siddiqui; Vikram Vishal (Gas Science and Engineering, 2025)

Natural anthocyanin dye concentration through ultrathin polyester-amide hollow fiber forward osmosis membrane - Pranay Kumar; Nayan Nandha; Mrinmoy Mondal; Puyam S. Singh (Chemical Engineering Journal, 2025)

The effect of enhanced glycolysis on cardiac aging - Anna Faakye; Kylene M. Harold; Satoshi Matsuzaki; Atul Pranay; Maria F. Mendez Garcia; Brooke L. Loveland; Sandra N. Rigsby; Frederick F. Peelor; Craig Eyster; Benjamin F. Miller; Timothy M. Griffin; Michael Kinter; et al. (GeroScience, 2025)
Cardiac aging is associated with metabolic changes, including an increased reliance on glycolysis, and an increased susceptibility to cardiovascular diseases. This study explores the relationship between enhanced cardiac glycolysis and aging using the Glyco Hi mouse model, characterized by constitutively elevated glycolysis. We compared cardiac function, metabolism, mitochondrial performance, and hallmarks of aging between aged (21 and 24 months) Glyco Hi and wild-type (WT) mice across sexes. Our findings reveal modest reductions in cardiac function in aged Glyco Hi mice compared to WT mice, with sex-specific differences in heart size and collagen concentration. Female Glyco Hi hearts exhibited hypertrophy without fibrosis, while males showed elevated collagen levels. Whole-body metabolic assessments revealed similar energy expenditure and respiratory patterns across genotypes, with females displaying less circadian-associated variation in metabolism. Mitochondrial analyses showed that aged Glyco Hi hearts maintained metabolic adaptations favoring glycolysis but did not exhibit significant bioenergetic dysfunction or oxidative stress. Pyruvate dehydrogenase activity, initially elevated in younger Glyco Hi hearts, normalized to WT levels with age. Proteomic and metabolomic analyses highlighted distinct profiles between genotypes, with Glyco Hi hearts exhibiting increased glycolytic enzyme levels and reduced abundance of fatty acid oxidation proteins. Despite these differences, indicators of oxidative stress, proteostasis, and cellular senescence were comparable between genotypes, suggesting no acceleration of aging-related dysfunction. This study demonstrates that increased cardiac glycolysis alone does not suffice to drive accelerated cardiac aging. Instead, metabolic and functional changes in aged Glyco Hi hearts reflect adaptations rather than pathological declines, providing insights into potential metabolic targets for interventions against cardiac aging.

Formulation of Nanogel Loaded with Lantana montevidensis-Incorporated Silver Nanoparticles: A Bio-Inspired Approach to Rheumatoid Arthritis Therapy - Sourabh Malabade; Preeti Salve; Pranay S. Shirke (Journal of Pharmaceutical Innovation, 2025)

Wild introgression lines of Oryza nivara as potential donor for yield and seedling vigour traits and mapping associated genomic regions - D. Sai Teja; Divya Balakrishnan; P. Magudeeswari; Sonali Kar; P. Arun Kumar; G. Pranay; R. Pushpa; Kalyani M. Barbadikar; L. V. Subba Rao; N. Sarla; S. V. SaiPrasad; R. M. Sundaram (Euphytica, 2025)

COP29: achieving net zero through financial sustainability - Pranay Arora (Environmental Sustainability, 2025)
Conference of Parties (COP) provide a critical platform to global leaders to review and discuss targets related to achieving the Paris Agreement, and the sustainable development goals. This yearly summit has become a key part of the policy-making sector, allowing actors from different sectors to come together and take action on anthropogenic climate change. At the recently held COP29 summit, important decisions regarding financial flow in the climate sector were taken. These goals aim to increase funding for climate actions, particularly in developing nations, and help reduce human and economic damage from anthropogenic weather disasters. While the decisions promise a huge increase in channeling of funds to developing nations, some critical issues remain in the targets. This article aims to assess the outcomes and decisions taken at COP29 and their benefits and disadvantages, particularly for the developing nations. It also discusses steps that can be taken to further improve these outcomes.

Advanced Normal-Phase HPTLC Profiling of Eltrombopag Olamine with Automated Development and Box-Behnken Optimizations - Pranay M. Hadole; Saurabh B. Ganorkar; Suraj R. Chaudhari; Vaishali N. Sonawane; Preeti S. Bobade; Amod S. Patil; Atul A. Shirkhedkar (Journal of Pharmaceutical Innovation, 2025)

Phytoremediation of perfluoroalkyl and polyfluoroalkyl substances (PFAS): Insights on plant uptake, omics analysis, contaminant detection and biomass disposal - Davide Marzi; Francesco Valente; Sophia Luche; Cristina Caissutti; Andrea Sabia; Ilaria Capitani; Giuseppe Capobianco; Silvia Serranti; Antonio Masi; Anna Panozzo; Ada Ricci; Pranay Kumar Bolla; et al. (Science of The Total Environment, 2025)

Development of an electric cabbage harvester: an eco-friendly solution for mechanical harvesting of cabbage - Pranay Sarkar; Hifjur Raheman (Clean Technologies and Environmental Policy, 2025)

Status of visfatin in female reproductive function under normal and pathological conditions: a mini review - Lalrawngbawli Annie; Pranay Punj Pankaj; Rajesh Kumar Kharwar; Ajit Singh; Vikas Kumar Roy (Molecular Biology Reports, 2024)

Bridging systems thinking mindsets and farm management: The role of agricultural conservation planning in farmers’ adoption of conservation practices - Junyu Lu; Sarah P. Church; Pranay Ranjan; Emily M. Usher; Linda S. Prokopy (Journal of Rural Studies, 2024)

A comprehensive review on the pharmacological role of gut microbiome in neurodegenerative disorders: potential therapeutic targets - Namra Aziz; Pranay Wal; Aman Patel; Harshit Prajapati (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Detailed review on phytosomal formulation attenuating new pharmacological therapies - Jyotsana Dwivedi; Pranjal Sachan; Pranay Wal; Sumeet Dwivedi; Mukesh Chandra Sharma; Surada Prakash Rao (Advances in Traditional Medicine, 2024)

Linkage mapping and quantitative trait loci detection for seedling vigor and grain size in advanced backcross introgression lines from wild accessions of Oryza nivara - P. Magudeeswari; Divya Balakrishnan; Yoshimichi Fukuta; Hiroki Saito; D. Saitheja; G. Pranay; R. Padmashree; Kalyani M Barbadikar; Jyothi Badri; P. Senguttuvel; K. Sruthi; D. Ladhalakshmi; et al. (Genetic Resources and Crop Evolution, 2024)

MAGE: Microgrids with Advanced Grid Efficiency through Battery-Aware EV management - Ritam Sarkar; Pranay Kumar Saha; Samrat Mondal; Arijit Mondal (Sustainable Cities and Society, 2024)

Developing biomass augmentation strategy for cultivation of Marvania coccoides using fruit waste and wastewater based growth medium for biodiesel production - Pranay Awathare; Sinchan Hait; Sushant Gawali; Manoranjan Nayak; Neelamegam Ramesh Kumar; Abhishek Guldhe (Bioresource Technology, 2024)

Characterization of palmitic acid toxicity induced insulin resistance in HepG2 cells. - Sajad Malik; Shrirang Inamdar; Jhankar Acharya; Pranay Goel; Saroj Ghaskadbi (Toxicology in Vitro, 2024)

Understanding the rock slope stability along Malshej Ghat, India, using rock mass characterisation and block shape classification techniques - Saurabh Prakash Aher; Durga Prasanna Mohanty; Pranay Vilas Bhapkar; Sarada Prasad Pradhan; Vikram Vishal (Journal of Earth System Science, 2024)

Exploring the Role of ‘Intermediaries’ between Non-Operating Landowners and Tenant Farmers in Promoting Conservation on Rented Farmland - Pranay Ranjan; Miles Johnson; Mazie Bernard; Hans Schmitz; Seth Harden; Linda Prokopy (Environmental Management, 2024)

Genetic characterization of minor carp (Labeo gonius) from Indian rivers revealed through mitochondrial ATPase 6/8 and D-loop region analysis: implications for conservation and management - Suvra Roy; Bijay Kumar Behera; Ramya V. L.; Ajay Kumar Rout; Vikash Kumar; Pranay Kumar Parida; Asim Kumar Jana; Pronob Das; Dharmendra Kumar Meena; Dibakar Bhakta; Absar Alam; Basanta Kumar Das; et al. (Frontiers in Marine Science, 2024)
India is the habitat of many freshwater fish species that make a significant contribution to endemism. However, the native species population is declining at a very fast rate due to pollution, habitat loss or degradation, new species introduction, hydrologic alterations, and overfishing. The minor carp, Labeo gonius , is one of the important fish species in the Indian river systems and holds enormous potential in culture fisheries. Therefore, the precise status of population structure is a prerequisite for the management of the species. In the present study, we assessed the potential of mtDNA ATPase 6/8 and D-loop regions as markers to determine the genetic diversity and phylogeography of L. gonius from Indian rivers. We have selected five major Indian rivers for investigation which could represent geographically distant populations of the studied fish. A total of 210 ATPase 6/8 sequences (842 bp) and 203 D-loop region sequences (683 bp) of L. gonius from the five major Indian rivers were submitted to NCBI. Results revealed that ATPase 6/8 has 17 haplotypes and 70 polymorphic sites with an overall haplotype diversity of 0.560 ± 0.036 and nucleotide diversity of 0.00347 ± 0.00. Furthermore, D-loop analysis revealed 58 haplotypes, 67 polymorphic sites, 0.954 ± 0.006 overall haplotype diversity, and 0.01914 ± 0.00 nucleotide diversity. The hierarchical AMOVA analysis indicated that a high proportion of the genetic variation (76.46% and 70.22% for the D-loop and ATPase 6/8 regions, respectively) was attributed to among-population variation under gene pool-1 (considering all the stocks from Ganga, Brahmaputra, Teesta, Narmada, and Mahanadi as a single pool). Furthermore, in gene pool-2, samples were divided into two groups: group 1 (Himalayan rivers)—Ganga, Brahmaputra, and Teesta; and group 2 (peninsular rivers)—Narmada and Mahanadi. Genetic variations in the D-loop and ATPase 6/8 regions were found among populations within groups at 70.65% and 53.48%, respectively. Haplotype network analysis revealed that there were significant differences in distributions and frequencies. The observed unique haplotypes might be useful for differentiating the stocks. In brief, the present study suggested that the D-loop and ATPase 6/8 regions are potential markers and represent a significant contribution to the genetic characterization of the minor carp L. gonius from major Indian rivers. Moreover, the L. gonius population along the east coast especially in the Himalayan rivers (Ganga, Brahmaputra, and Teesta river basin) is found to be genetically more diverse. The results would provide a scientific basis for the assessment of fisheries resources and management of this important species.

COP28: ambitions, realities, and future - Pranay Arora (Environmental Sustainability, 2024)

Characterization of Novel Antimicrobial Peptides from the Epidermis of Clarias batrachus Catfish - Bupesh Giridharan; Amutha Chinnaiah; Konda Mani Saravanan; Sudharsan Parthasarathy; Kishore Kumar Meenakshi Sundaram; Siva Vijayakumar Tharumasivam; Pranay Punj Pankaj; Archunan Govindaraju; Dayalan Haripriya; Uttam Kumar Sahoo (International Journal of Peptide Research and Therapeutics, 2024)

Portable system to detect starch adulteration in turmeric using NIR spectroscopy - Madhusudan G. Lanjewar; Pranay P. Morajkar; Jivan S. Parab (Food Control, 2024)

SDG 14: life below water- viable oceans necessary for a sustainable planet - Naveen Kumar Arora; Isha Mishra; Pranay Arora (Environmental Sustainability, 2023)

Chemoprofiling and antioxidant activity of edible curcuma species - Akanksha Jain; Parag Jain; Sonia Bajaj; Ashish Majumdar; Pranay Soni (Food and Humanity, 2023)

Peripheral MC1R Activation Modulates Immune Responses and is Neuroprotective in a Mouse Model of Parkinson’s Disease - Pranay Srivastava; Shuhei Nishiyama; Fang Zhou; Sonia H. Lin; Akriti Srivastava; Chienwen Su; Yuehang Xu; Weiyi Peng; Michael Levy; Michael Schwarzschild; Xiqun Chen (Journal of Neuroimmune Pharmacology, 2023)
Background Melanocortin 1 receptor ( MC1R ) is a key pigmentation gene, and loss-of-function of MC1R variants that produce red hair may be associated with Parkinson’s disease (PD). We previously reported compromised dopaminergic neuron survival in Mc1r mutant mice and dopaminergic neuroprotective effects of local injection of a MC1R agonist to the brain or a systemically administered MC1R agonist with appreciable central nervous system (CNS) permeability. Beyond melanocytes and dopaminergic neurons, MC1R is expressed in other peripheral tissues and cell types, including immune cells. The present study investigates the impact of NDP-MSH, a synthetic melanocortin receptor (MCR) agonist that does not cross BBB, on the immune system and the nigrostriatal dopaminergic system in mouse model of PD. Methods C57BL/6 mice were treated systemically with MPTP.HCl (20 mg/kg) and LPS (1 mg/kg) from day 1 to day 4 and NDP-MSH (400 µg/kg) or vehicle from day 1 to day 12 following which the mice were sacrificed. Peripheral and CNS immune cells were phenotyped and inflammatory markers were measured. The nigrostriatal dopaminergic system was assessed behaviorally, chemically, immunologically, and pathologically. To understand the role of regulatory T cells (Tregs) in this model, CD25 monoclonal antibody was used to deplete CD25 + Tregs. Results Systemic NDP-MSH administration significantly attenuated striatal dopamine depletion and nigral dopaminergic neuron loss induced by MPTP + LPS. It improved the behavioral outcomes in the pole test. Mc1r mutant mice injected with NDP-MSH in the MPTP and LPS paradigm showed no changes in striatal dopamine levels suggesting that the NDP-MSH acts through the MC1R pathway. Although no NDP-MSH was detected in the brain, peripheral, NDP-MSH attenuated neuroinflammation as observed by diminished microglial activation in the nigral region, along with reduced TNF-α and IL1β levels in the ventral midbrain. Depletion of Tregs was associated with diminished neuroprotective effects of NDP-MSH. Conclusions Our study demonstrates that peripherally acting NDP-MSH confers protection on dopaminergic nigrostriatal neurons and reduces hyperactivated microglia. NDP-MSH modulates peripheral immune responses, and Tregs may be involved in the neuroprotective effect of NDP-MSH.

A Review on Hydrogen Production from Biomass and Commercialization Assessment Through Technology Readiness Levels (TRLs) - Pranay Rajendra Lanjekar; Narayan Lal Panwar (BioEnergy Research, 2023)

An automatic pressure control system for precise spray pattern analysis on spray patternator - Manojit Chowdhury; E.V. Thomas; Ayushi Jha; Ajay Kushwah; Ramkishor Kurmi; Tapan Kumar Khura; Pranay Sarkar; Kiranmoy Patra (Computers and Electronics in Agriculture, 2023)

Highly water permeable ‘reverse osmosis’ polyamide membrane of folded nanoscale film morphology - Utpal G. Thummar; J. Jayalakshmi; Mayank Saxena; Yogesh Suva; Nayan Nandha; Pranay Kumar; Vinod K. Aswal; Puyam S. Singh (Journal of Water Process Engineering, 2023)

Anthropometric measures and arsenic methylation among pregnant women in rural northern Bangladesh - Tyler J.S. Smith; Ana Navas-Acien; Sarah Baker; Caryn Kok; Kate Kruczynski; Lindsay N. Avolio; Nora Pisanic; Pranay R. Randad; Rebecca C. Fry; Walter Goessler; Alexander van Geen; Jessie P. Buckley; et al. (Environmental Research, 2023)

Stable and fast oil recovery by environmentally friendly and easy to synthesize pristine graphitic carbon nitride - Pranay Gandharapu; Rashmi Chandrabhan Shende; Manoj K. Jangid; Amartya Mukhopadhyay (Clean Technologies and Environmental Policy, 2023)

Hybrid method for accurate starch estimation in adulterated turmeric using Vis-NIR spectroscopy - Madhusudan G. Lanjewar; Pranay P. Morajkar; Jivan S. Parab (Food Additives & Contaminants: Part A, 2023)

Preliminary observations on the coral reef communities in Angria Bank, an isolated carbonate bank in the Northern Indian Ocean - Ravindran J.; Pranay Sawant; Manikandan B.; Ingole B.S.; Dhivya P.; Periasamy R.; Sundaresh; Sharma R. (Regional Studies in Marine Science, 2023)

Correction: The Social Factors Influencing Cover Crop Adoption in the Midwest: A Controlled Comparison - Ruxandra Popovici; Pranay Ranjan; Mazie Bernard; Emily Marie Usher; Kris Johnson; Linda Stalker Prokopy (Environmental Management, 2023)

The Social Factors Influencing Cover Crop Adoption in the Midwest: A Controlled Comparison - Ruxandra Popovici; Pranay Ranjan; Mazie Bernard; Emily Marie Usher; Kris Johnson; Linda Stalker Prokopy (Environmental Management, 2023)

Developing a framework for achieving optimal sustainability and resilience in circular sharing network - K. E. K. Vimal; Mohammed Faaz Shaikh; Ananya Pranay Chouhan; Jayakrishna Kandasamy (Environment, Development and Sustainability, 2023)

Skeletal and cardiac muscle have different protein turnover responses in a model of right heart failure - Danielle R. Bruns; Benjamin D. McNair; Frederick F. Peelor; Agnieszka K. Borowik; Atul Pranay; Aykhan Yusifov; Benjamin F. Miller (GeroScience, 2023)

The loss of cardiac SIRT3 decreases metabolic flexibility and proteostasis in an age-dependent manner - Ping Li; Maria F. Newhardt; Satoshi Matsuzaki; Craig Eyster; Atul Pranay; Frederick F. Peelor; Albert Batushansky; Caroline Kinter; Kumar Subramani; Sandeep Subrahmanian; Jasimuddin Ahamed; Pengchun Yu; et al. (GeroScience, 2023)
SIRT3 is a longevity factor that acts as the primary deacetylase in mitochondria. Although ubiquitously expressed, previous global SIRT3 knockout studies have shown primarily a cardiac-specific phenotype. Here, we sought to determine how specifically knocking out SIRT3 in cardiomyocytes (SIRTcKO mice) temporally affects cardiac function and metabolism. Mice displayed an age-dependent increase in cardiac pathology, with 10-month-old mice exhibiting significant loss of systolic function, hypertrophy, and fibrosis. While mitochondrial function was maintained at 10 months, proteomics and metabolic phenotyping indicated SIRT3 hearts had increased reliance on glucose as an energy substrate. Additionally, there was a significant increase in branched-chain amino acids in SIRT3cKO hearts without concurrent increases in mTOR activity. Heavy water labeling experiments demonstrated that, by 3 months of age, there was an increase in protein synthesis that promoted hypertrophic growth with a potential loss of proteostasis in SIRT3cKO hearts. Cumulatively, these data show that the cardiomyocyte-specific loss of SIRT3 results in severe pathology with an accelerated aging phenotype.

Kinetic proteomics identifies targeted changes in liver metabolism and the ribo-interactome by dietary sulfur amino acid restriction - William O. Jonsson; Agnieszka K. Borowik; Atul Pranay; Michael T. Kinter; Emily T. Mirek; Jordan L. Levy; Elizabeth M. Snyder; Benjamin F. Miller; Tracy G. Anthony (GeroScience, 2023)
Dietary sulfur amino acid restriction (SAAR) protects against diet-induced obesity, extends healthspan, and coincides with an overall reduction in hepatic protein synthesis. To explore the underpinnings of SAAR-induced slowed growth and its impact on liver metabolism and proteostasis, we resolved changes in hepatic mRNA and protein abundances and compared synthesis rates of individual liver proteins. To achieve this, adult male mice were provided deuterium-labeled drinking water while freely consuming either a regular-fat or high-fat diet that was SAA restricted. Livers from these mice and their respective dietary controls were used to conduct transcriptomic, proteomic, and kinetic proteomic analyses. We found that remodeling of the transcriptome by SAAR was largely agnostic to dietary fat content. Shared signatures included activation of the integrated stress response alongside alterations in metabolic processes impacting lipids, fatty acids, and amino acids. Changes to the proteome correlated poorly with the transcriptome, and yet, functional clustering of kinetic proteomic changes in the liver during SAAR revealed that the management of fatty acids and amino acids were altered to support central metabolism and redox balance. Dietary SAAR also strongly influenced the synthesis rates of ribosomal proteins and ribosome-interacting proteins regardless of dietary fat. Taken together, dietary SAAR alters the transcriptome and proteome in the liver to safely manage increased fatty acid flux and energy use and couples this with targeted changes in the ribo-interactome to support proteostasis and slowed growth.

RETRACTED ARTICLE: Nanosilver-functionalized polysaccharides as a platform for wound dressing - Syam Mohan; Pranay Wal; Kamla Pathak; Madhusmruti Khandai; Tapan Behl; Hassan A. Alhazmi; Gulrana Khuwaja; Asaad Khalid (Environmental Science and Pollution Research, 2023)

Sustainable treatment of saline dye wastewater and resource recovery with flux-recoverable hollow fiber of antifouling ‘water channel’ - Pranay Kumar; Utpal G. Thummar; Nayan H. Nandha; Puyam S. Singh (Desalination, 2023)

A comprehensive review on hydrogen production through thermochemical conversion of biomass for energy security - Pranay Rajendra Lanjekar; Narayan Lal Panwar; Chitranjan Agrawal (Bioresource Technology Reports, 2023)

COP27: a summit of more misses than hits - Pranay Arora; Naveen Kumar Arora (Environmental Sustainability, 2023)

Fabrication of gold nanodots decorated on 2D tungsten sulfide (Au-WS2) photoanode for simultaneous oxidation of phenol and arsenic (III) from industrial wastewater - G. Bharath; K. Rambabu; Bayan Alqassem; Pranay P. Morajkar; Mohammad Abu Haija; Ashok Kumar Nadda; Vijai Kumar Gupta; Fawzi Banat (Chemical Engineering Journal, 2023)

Flood susceptible surface detection using geospatial multi-criteria framework for management practices - Pranay Paul; Rumki Sarkar (Natural Hazards, 2022)

Role of dynamic downstream hydraulic geometry on season-wise channel behavior pattern in the floodplains of Nagar Basin, India - Pranay Paul; Rumki Sarkar (Sustainable Water Resources Management, 2022)

Integration of pen aquaculture into ecosystem-based enhancement of small-scale fisheries in a macrophyte dominated floodplain wetland of India - Gunjan Karnatak; Basanta Kumar Das; Uttam Kumar Sarkar; Simanku Borah; Aparna Roy; Pranay Parida; Lianthuamluaia Lianthuamluaia; Archan Kanti Das; Bijay Kumar Behera; Arun Pandit; Amiya Kumar Sahoo; Birendra Kumar Bhattacharjya; et al. (Environmental Science and Pollution Research, 2022)

How does co-produced research influence adaptive capacity? Lessons from a cross-case comparison - Sarah P. Church; Chloe B. Wardropper; Emily Usher; Liam F. Bean; Ashlie Gilbert; Francis R. Eanes; Jessica D. Ulrich-Schad; Nicholas Babin; Pranay Ranjan; Jackie M. Getson; Laura A. Esman; Linda S. Prokopy (Socio-Ecological Practice Research, 2022)

Unravelling the molecular mechanism of mutagenic factors impacting human health - Keshav Goyal; Harsh Goel; Pritika Baranwal; Aman Dixit; Fahad Khan; Niraj Kumar Jha; Kavindra Kumar Kesari; Pratibha Pandey; Avanish Pandey; Mercilena Benjamin; Ankit Maurya; Vandana Yadav; et al. (Environmental Science and Pollution Research, 2022)

Classification of SARS-CoV-2 viral genome sequences using Neurochaos Learning - N. B. Harikrishnan; S. Y. Pranay; Nithin Nagaraj (Medical & Biological Engineering & Computing, 2022)

Assimilation of Remote Sensing Data into Crop Growth Model for Yield Estimation: A Case Study from India - Murali Krishna Gumma; M. D. M. Kadiyala; Pranay Panjala; Shibendu S. Ray; Venkata Radha Akuraju; Sunil Dubey; Andrew P. Smith; Rajesh Das; Anthony M. Whitbread (Journal of the Indian Society of Remote Sensing, 2022)

Unfolding the Role of BDNF as a Biomarker for Treatment of Depression - Tarapati Rana; Tapan Behl; Aayush Sehgal; Pranay Srivastava; Simona Bungau (Journal of Molecular Neuroscience, 2021)

Structural based screening of potential inhibitors of SMAD4: a step towards personalized medicine for gall bladder and other associated cancers - Rakesh Kumar; Rahul Kumar; Pranay Tanwar (Molecular Diversity, 2021)

Antioxidant and antibacterial activity of Gelidium pusillum (Stackhouse) against Aeromonas caviae and its applications in aquaculture - Pranay Agarwal; Pooja Kayala; Natrajan Chandrasekaran; Amitava Mukherjee; Shreshtha Shah; John Thomas (Aquaculture International, 2021)

Enhancing the safety of frontline healthcare workers during coronavirus disease: a novel real-time remote audiovisual aided doffing approach - Manju Dhandapani; Sukhpal Kaur; Karobi Das; Rashmi Ranjan Guru; Manisha Biswal; Pranay Mahajan; Vipin Koushal; Goverdhan D. Puri (Infectious Diseases, 2021)

Climate change coverage in the United States media during the 2017 hurricane season: implications for climate change communication - Roberta Weiner; Sarah P. Church; Junyu Lu; Laura A. Esman; Jackie M. Getson; Michelle Fleckenstein; Brennan Radulski; Pranay Ranjan; Emily Usher; Linda S. Prokopy; Linda Pfeiffer (Climatic Change, 2021)

Sensitization of hepatocellular carcinoma cells towards doxorubicin and sorafenib is facilitated by glucose-dependent alterations in reactive oxygen species, P-glycoprotein and DKK4 - Surbhi Chouhan; Snahlata Singh; Dipti Athavale; Pranay Ramteke; Muralidharan Vanuopadath; Bipin G Nair; Sudarslal Sadasivan Nair; Manoj Kumar Bhat (Journal of Biosciences, 2020)

Elucidation of genotype–environment interactions and genetic stability parameters for yield, quality and agromorphological traits in ashwagandha (Withania somnifera (L.) Dunal) - MITHLESH KUMAR; MANUBHAI PATEL; RAVINDRASINGH CHAUHAN; CHANDRESH TANK; SATYANARAYAN SOLANKI; PRAVINBHAI PATEL; HITENDRA BHADAURIA; RAMAN GAMI; KAREN PACHCHIGAR; NISHIT SONI; PRANAY PATEL; ANUJ SINGH; et al. (Journal of Genetics, 2020)

Numerical Investigation of Squeezing in Underground Hard Rock Mines - Pranay Yadav; Shailendra Sharan (Rock Mechanics and Rock Engineering, 2019)

Correction to: Remote sensing and in situ-based assessment of rapidly growing South Lhonak glacial lake in eastern Himalaya, India - R. K. Sharma; Pranay Pradhan; N. P. Sharma; D. G. Shrestha (Natural Hazards, 2018)

Remote sensing and in situ-based assessment of rapidly growing South Lhonak glacial lake in eastern Himalaya, India - R. K. Sharma; Pranay Pradhan; N. P. Sharma; D. G. Shrestha (Natural Hazards, 2018)

Protective Effect of Curcumin by Modulating BDNF/DARPP32/CREB in Arsenic-Induced Alterations in Dopaminergic Signaling in Rat Corpus Striatum - Pranay Srivastava; Yogesh K. Dhuriya; Richa Gupta; Rajendra K. Shukla; Rajesh S. Yadav; Hari N. Dwivedi; Aditya B. Pant; Vinay K Khanna (Molecular Neurobiology, 2018)

Midwestern US Farmers Perceive Crop Advisers as Conduits of Information on Agricultural Conservation Practices - Francis R. Eanes; Ajay S. Singh; Brian R. Bulla; Pranay Ranjan; Linda S. Prokopy; Mary Fales; Benjamin Wickerham; Patrick J. Doran (Environmental Management, 2017)

Protective Role of Quercetin in Cadmium-Induced Cholinergic Dysfunctions in Rat Brain by Modulating Mitochondrial Integrity and MAP Kinase Signaling - Richa Gupta; Rajendra K. Shukla; Lalit P. Chandravanshi; Pranay Srivastava; Yogesh K. Dhuriya; Jai Shanker; Manjul P. Singh; Aditya B. Pant; Vinay K. Khanna (Molecular Neurobiology, 2017)

Genetic variation in retinal vascular patterning predicts variation in pial collateral extent and stroke severity - Pranay Prabhakar; Hua Zhang; De Chen; James E. Faber (Angiogenesis, 2015)

Are “universal” DNA primers really universal? - Pranay Sharma; Tsuyoshi Kobayashi (Journal of Applied Genetics, 2014)

Synthesis and antimicrobial screening of some novel chalcones and flavanones substituted with higher alkyl chains - Uppuluri Venkata Mallavadhani; Laxmidhar Sahoo; Koochana Pranay Kumar; Upadyayula Suryanarayana Murty (Medicinal Chemistry Research, 2014)

Synthesis, antimicrobial and cytotoxic activities of novel 4-trifluoromethyl-(1,2,3)-thiadiazolo-5-carboxylic acid hydrazide Schiff’s bases - P. Sambasiva Rao; C. Kurumurthy; B. Veeraswamy; G. Santhosh kumar; B. Narsaiah; K. Pranay Kumar; U. S. N. Murthy; Santosh Karnewar; Srigiridhar Kotamraju (Medicinal Chemistry Research, 2013)

Cellular differentiation, regeneration, and secondary metabolite production in medicinal Picrorhiza spp. - Tapan K. Mondal; Pranay Bantawa; Bipasa Sarkar; Parthodev Ghosh; Pradeep K. Chand (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Erratum to: Phylogenetic framework and molecular signatures for the class Chloroflexi and its different clades; proposal for division of the class Chloroflexi class. nov. into the suborder Chloroflexineae subord. nov., consisting of the emended family Oscillochloridaceae and the family Chloroflexaceae fam. nov., and the suborder Roseiflexineae subord. nov., containing the family Roseiflexaceae fam. nov. - Radhey S. Gupta; Pranay Chander; Sanjan George (Antonie van Leeuwenhoek, 2013)

Phylogenetic framework and molecular signatures for the class Chloroflexi and its different clades; proposal for division of the class Chloroflexi class. nov. into the suborder Chloroflexineae subord. nov., consisting of the emended family Oscillochloridaceae and the family Chloroflexaceae fam. nov., and the suborder Roseiflexineae subord. nov., containing the family Roseiflexaceae fam. nov. - Radhey S. Gupta; Pranay Chander; Sanjan George (Antonie van Leeuwenhoek, 2013)

Changes of growth, photosynthesis and alteration of leaf antioxidative defence system of tea [Camellia sinensis (L.) O. Kuntze] seedlings under aluminum stress - Mainaak Mukhopadyay; Pranay Bantawa; Akan Das; Bipasa Sarkar; Biswajit Bera; Parthadeb Ghosh; Tapan Kumar Mondal (BioMetals, 2012)

Evaluation of Fermentation Efficiency of Yeast Strains and their Effect on Quality of Young Wines - A. K. Sharma; Pranay Nath Singh; S. D. Sawant (Indian Journal of Microbiology, 2012)

Estimating the Size of Tendu Leaf and Bidi Trade Using a Simple Back-of-the-Envelop Method - Pranay Lal (Ambio, 2012)

Tumour necrosis factor alpha and interleukin 10 gene polymorphisms and the risk of ischemic stroke in south Indian population - SHEHNAZ SULTANA; VENKATA K. KOLLA; YASOVANTHI JEEDIGUNTA; PRANAY K. PENAGALURU; SINDHU JOSHI; P. USHA RANI; P. P. REDDY (Journal of Genetics, 2011)

CsF–Celite catalyzed facile N-alkylation of 2(3H)-benzoxazolones and antimicrobial properties of 2-substituted benzoxazole and 3-substituted-2(3H)-benzoxazolone derivatives - M. S. R. Murty; Kesur R. Ram; Rayudu Venkateswara Rao; J. S. Yadav; U. S. N. Murty; K. Pranay Kumar (Medicinal Chemistry Research, 2011)

Association of CYP1A1 Gene Polymorphism with Ischemic Stroke in South Indian Population - Shehnaz Sultana; Venkata Karunakar Kolla; Vidyullatha Peddireddy; Yasovanthi Jeedigunta; Pranay K. Penagaluru; Sindhu Joshi; Usha Rani Penagaluru; Pardhananda Reddy Penagaluru (Translational Stroke Research, 2011)

A neuronal network for the logic of Limax learning - Pranay Goel; Alan Gelperin (Journal of Computational Neuroscience, 2006)